Chad : Joint Bank-Fund Debt Sustainability Analysis, 2018 Update - International Development Association (Washington, DC: World Bank, 2018)
Following the restructuring of the debt to Glencore and the progress made in clearing external arrears, debt vulnerabilities declined significantly, and the external risk rating has been upgraded to high. The debt sustainability analysis (DSA) shows that all debt burden indicators, except the debt-service-to-revenue ratio which has minor and temporary breaches, are below their respective thresholds in the baseline from 2018 onwards. The debt-service-to-revenue ratio, falls below the threshold in 2019 and remains so throughout the projection period, except for minor breaches in 2020 and 2021. Overall, total public debt vulnerabilities are elevated although the present value (PV) of the public debt-to- gross domestic product (GDP) ratio remains on a downward trajectory. The fixed primary balance scenario, which keeps the primary deficit-to-GDP ratio unchanged from 2017, shows the debt ratio declining at a slower pace throughout the forecast period, further highlighting the need to adhere to the prudent fiscal policy framework underpinning the International Monetary Fund (IMF)-supported program. Adoption and implementation of an appropriate debt management strategy, while making progress in economic diversification will further reduce vulnerabilities.